Modifikasi Penambahan Lube Oil Pump Pada Pulverizer PLTU Suralaya Unit 1-4 - Eko Sulistyo; Fahrudin Sinatrya (JURNAL POWERPLANT, 2015)
Suralaya Power Plant unit 1-4 using coal as fuel, before a coal burned in the living room fuel first crushed using pulverizer (mill).part of Mill has a function to alter the current round of torque electric motor is gearbox, in gearbox pulverizer there are gear - accessible teeth and safeguards that require lubrication circulation to minimize wears a so-called system lube oil pulverizer.When pulverizer are currently operating system and disturbance in lubricant oils pressure pulverizer resulting in low, then Mill stopped operating in tibatiba (trip). Mill trip will reduce coal supply toward boiler system, so that it will reduce the ability boiler in producing steam room and not directly affected electricity production.After understand pulverizer operations and system pelumasanya Because of that, in order to prevent pulverizer trip, the solution is menambahan gas reserves pemipaanya (piping) in pairs in parallel with pumps and will be operated if pressure lubricant low when pulverizer operate.pump and electric motor initiators suffers from specification is almost same or identical with valve isolation and valve system in the direction.pengabelan (wiring/cable length according) will also be modified to support pump operation reserves.